Vibrational spectra of chemical and isotopic variants of oxyluciferin, the light emitter of firefly bioluminescence - Maltsev, Oleg V; Yue, Ling; Rebarz, Mateusz; Hintermann, Lukas; Sliwa, Michel; Ruckebusch, Cyril; Pejov, Ljupčo; Liu, Ya-Jun; Naumov, Panče (My University, 2014)
The chemical complexity of oxyluciferin (OxyLH2), the light-emitting molecule in the bioluminescence of fireflies, originates from the possibility of keto/enol tautomerism and single or double deprotonation. Herein, we present detailed infrared spectroscopic analysis of OxyLH2 and several of its chemical isomers and isotopomers. To facilitate the future characterization of its biogenic forms, we provide accurate assignments of the solid-state and solution FTIR spectra of OxyLH2 based on comparison to six isotopically labeled variants ([2-(13)C]-OxyLH2, [3-(15)N]-OxyLH2, [4-(13)C]-OxyLH2, [5-(13)C]-OxyLH2, [2'-(13)C]-OxyLH2, [3'-(15)N]-OxyLH2), five closely related structural analogues, and theoretically computed spectra. The computed DFT harmonic vibrational force fields (B3LYP and M06 functionals with basis sets of varying flexibility up to 6-311++G**) reproduce well the observed shifts in the IR spectra of both isotopically labeled and structurally related analogues.